TRAINING FOR MAKING CORN DRYER EQUIPMENT USING UV PLASTIC IN WEST KOYA VILLAGE - Joni, Joni; Sri Werdhani, Anastasia (LPPM Univ. Ibn Khaldun Bogor, 2023)
The Koya West area is an agricultural center area in the city of Jayapura. After harvest, some of these agricultural products are sold directly to the market or to consumers, but some must go through a drying process, including corn, shallots and coconut. The drying process is still traditional, namely by relying on solar energy. Problems that occur when drying is done during the rainy season. In addition, the drying process requires a large area because the crops are just spread out on the ground with tarpaulin. In addition to being unhygienic, it will also be very inconvenient when it rains and farmers must save the crops that are in the sun so that they are not damaged. The purpose of this activity is to provide training and assistance in making dryers using UV plastic.